Resource Utilization, Innovation, and MSME Performance: A Circular Economy Perspective - Utami, Suci; Siskawati, Eka; Fauzi, Nurul (International Ecsis Association, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are critical drivers of economic growth and innovation, particularly in emerging economies like Indonesia. However, they face persistent challenges such as limited resources, low innovation capacity, and growing pressure to meet environmental sustainability standards. This study investigates the impact of circular economy (CE) practices—specifically resource utilization and innovation & learning—on the business and socio-environmental performance of MSMEs in Padang City, Indonesia. Drawing upon the Natural Resource-Based View (NRBV), the study posits that sustainable resource management and organizational learning can serve as strategic capabilities for long-term competitive advantage. A quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) was employed, with data collected from 70 MSMEs via an online questionnaire. The results reveal that both resource utilization and innovation & learning significantly and positively affect business success and social-environmental performance. These findings underscore the importance of integrating sustainability-oriented innovations and resource efficiency into MSME operations. The study contributes to the limited empirical research linking NRBV and CE practices within MSMEs in emerging markets. It offers practical implications for policy-makers and business development programs aiming to foster sustainable competitiveness and inclusive growth through innovation and environmental stewardship in the MSME sector.